2023
DOI: 10.1002/anie.202303463
|View full text |Cite
|
Sign up to set email alerts
|

Customizable Supraparticles Constructed from Catechol‐Terminated Molecular Building Blocks with Controllable Intermolecular Interactions**

Abstract: Colloidal supraparticles integrated with multicomponent primary particles come with emerging or synergetic functionalities. However, achieving the functional customization of supraparticles remains a great challenge because of the limited options of building blocks with tailorability and functional extensibility. Herein, we developed a universal approach to construct customizable supraparticles with desired properties from molecular building blocks obtained by the covalent conjugation of catechol groups with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
(2 reference statements)
0
14
0
Order By: Relevance
“…In this strategy, we fabricated zinc oxide (ZnO) on the SNP surface, which was later converted to ZIF-90 in the presence of 2-ICA. This is similar to the template-based synthesis of supraparticles; 24 here, SNP acts as a template for the growth of ZIF-90 nanoparticles. Dox was utilized as a model drug to investigate drug delivery and anti-cancer efficacy in breast cancer cells.…”
Section: Introductionmentioning
confidence: 79%
“…In this strategy, we fabricated zinc oxide (ZnO) on the SNP surface, which was later converted to ZIF-90 in the presence of 2-ICA. This is similar to the template-based synthesis of supraparticles; 24 here, SNP acts as a template for the growth of ZIF-90 nanoparticles. Dox was utilized as a model drug to investigate drug delivery and anti-cancer efficacy in breast cancer cells.…”
Section: Introductionmentioning
confidence: 79%
“…[5,11,17,18] Metal-phenolic networks (MPNs) are metal-organic materials constructed from metal ions and natural polyphenols, [19,20] where the physiochemical properties and functional performance can be tailored by careful selection of the metal ions and phenolic ligands. [21][22][23] MPNs have exhibited translational potential owing to their rapid formation (less than 10 s) and versatile functionalities as well as feasible deposition on a wide range of inorganic, organic, and biological substrates. For example, we have previously demonstrated that MPNs can form biomimetic nanocloaks on the surface of individual bacteria, [24] yeast, [25] and mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical self-assembly from simple to complex is the most basic substance synthesis strategy in nature, which is of great significance for the in-depth understanding of the assembly process from molecular, nano to macro scale. [1][2][3] It also provides gynecology. [21][22][23] In recent years, the number of ovarian cancer patients worldwide has increased year by year, and the majority of ovarian cancer patients are already at the advanced stage when first diagnosed, and the five-year survival rate is less than 30%.…”
Section: Introductionmentioning
confidence: 99%